2003
DOI: 10.1210/me.2003-0118
|View full text |Cite
|
Sign up to set email alerts
|

Postendocytotic Trafficking of the Follicle-Stimulating Hormone (FSH)-FSH Receptor Complex

Abstract: Although the fates of the internalized hormone-receptor complexes formed by the lutropin/choriogonadotropin and the TSH receptors have been examined in some detail, much less is known about the fate of the internalized FSH-FSH receptor (FSHR) complex. Using biochemical and imaging approaches we show here that the majority of the internalized FSH-FSHR complex accumulates in endosomes and subsequently recycles back to the cell surface where the bound, intact hormone dissociates back into the medium. Only small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 62 publications
3
76
2
1
Order By: Relevance
“…However, the present findings and the lack of detectable FSH-gold particles within the recycling endosomal compartment differ from the results of Krishnamurthy et al (2003) who demonstrated that most of the FSH/FSH-R complex could be recycled to the plasma membrane. The reasons for this discrepancy are presently unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the present findings and the lack of detectable FSH-gold particles within the recycling endosomal compartment differ from the results of Krishnamurthy et al (2003) who demonstrated that most of the FSH/FSH-R complex could be recycled to the plasma membrane. The reasons for this discrepancy are presently unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…Functional Consequences of the hLHR/GIPC Interaction-A substantial portion of the hCG that is internalized by the hLHR is recycled back to the medium as undegraded hormone, and the density of cell surface hLHR remains relatively constant during many rounds of endocytosis of hCG (12,13,30). Both of these phenomena are dependent on the presence of Leu 683 and the C-terminal Cys 699 of the hLHR (Tables I and II).…”
Section: Resultsmentioning
confidence: 99%
“…internalized by the hLHR is recycled back to the medium in an undegraded form (13,26,30), the internalized hLHR localizes mostly to endosomes (13), and the loss of cell surface hLHR during the endocytosis of hCG in cells expressing the recombinant hLHR is minimal (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that a number of GPCRs require specific structural determinant(s) within their cytoplasmic domains in order to undergo efficient recycling to the plasma membrane (5)(6)(7)(8)(9)(10)(11). This process of "sequence-directed" recycling differs from "default" recycling of many other integral membrane proteins, such as the transferrin receptor, which occurs in the absence of any known cytoplasmic determinant and apparently by bulk membrane flow (12,13).…”
mentioning
confidence: 99%